BENTUK DAN TINGKAT PARTISIPASI PETANI PADI SAWAH DALAM KEGIATAN PENYULUHAN PERTANIAN DI KELURAHAN BARUGA KECAMATAN BARUGA - Rosida Safarudin; Dasmin Sidu; Yoenita Jayadisastra (Universitas Halu Oleo, 2023)
This study aims to determine the form of extension activities, the form and level of participation of wet-rice farmers in agricultural extension activities in Baruga Village. The research sample was 23 rice paddy farmers who were randomly selected from all 286 rice paddy farmers. Data were collected using interview and survey techniques. Data were analyzed qualitatively descriptively. The results showed that the extension activities of paddy rice farming were conducted in the form of integrated pest and disease control extension, balanced fertilization techniques according to site specifications, how to make organic fertilizer, tillage techniques, and crop rotation techniques in paddy fields. Forms of participation of wet-rice farmers in agricultural extension activities in the form of participation of ideas, social, and property. The level of participation of wet-rice farmers in agricultural extension activities is at the tokenism level. Because farmers have not been actively involved in the implementation of extension activities, especially in the preparation and evaluation stages of extension activities.